PEMBUATAN ALAT UKUR KONDUKTIVITAS BAHAN SATU DIMENSI - Samsudi Raharjo (JURNAL LITBANG, 2005)
This research is aimed at comparing between temperature conductivity grade which has been measured and material conductivity grade that will be researched through serial connection. By heating some material surface and measuring other material one, consequently hot temperature will occur. Whereas variables affecting the height of qk is A, dT/dX. To determine the height of  k is by means of calculating it based on the result of the research of material temperature which occurs in temperature detector. Subsequently, material conductivity, after its variables are known, is calculated by analyzing the regression and average of mean. The calculation result is following below :KA =15,682 , kB= 3,684 dan kC=5,535 watt/m oC. The calculation result is then calibrated with actual temperature, and the result is approaching copper, bronze and steel conductivity grade. Keyword : Conductor, Conductivity, Material.